2018
DOI: 10.1371/journal.pone.0198091
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of rifampicin and isoniazid resistance conferring mutations in Mycobacterium tuberculosis isolates from Uganda

Abstract: BackgroundAccurate diagnosis of tuberculosis, especially by using rapid molecular assays, can reduce transmission of drug resistant tuberculosis in communities. However, the frequency of resistance conferring mutations varies with geographic location of Mycobacterium tuberculosis, and this affects the efficiency of rapid molecular assays in detecting resistance. This has created need for characterizing drug resistant isolates from different settings to investigate frequencies of resistance conferring mutations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
32
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 55 publications
7
32
3
1
Order By: Relevance
“…Cigarette smoking was associated with MDR-TB. This is similar to other study findings [ 23 , 25 , 35 ]. Cigarette smoking directly causes ciliary dysfunction; this diminishes the immunity of individuals, which makes them prone to primary MDR-TB [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…Cigarette smoking was associated with MDR-TB. This is similar to other study findings [ 23 , 25 , 35 ]. Cigarette smoking directly causes ciliary dysfunction; this diminishes the immunity of individuals, which makes them prone to primary MDR-TB [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…None of the isolates showed complete mutation in more than one region. These results are in contrast to many reports across the globe, including some reports from East Africa, that had reported the most frequent mutations in codons 531 [24,25]. Although it had been Figure 2.…”
Section: Discussioncontrasting
confidence: 85%
“…suggested that variations may exist in different ethnic groups and geographic locations [24], most reports have shown mutations in codon 531 to be the most frequent, leading to the conclusion that codon 531 is the most prevalent region associated with rifampicin resistance [24][25][26][27][28][29][30]. Given the observation in this study, however, there may be need to carry out further investigation into the geographical variations.…”
Section: Discussionmentioning
confidence: 85%
“…similarly observed that 80% had kat G mutations and 6% had inh A mutations. [ 18 ] Tavakkoli and Nazemi also reported that in 17.24% and 82.76% of the strains, inh A genes and kat G genes, respectively, were responsible for INH resistance. [ 19 ] Niehaus et al .…”
Section: Discussionmentioning
confidence: 99%